Systemic Pharmacological Smoothened Inhibition Reduces Lung T-Cell Infiltration and Ameliorates Th2 Inflammation in a Mouse Model of Allergic Airway Disease - Yánez, Diana C.; Papaioannou, Eleftheria; Chawda, Mira M.; Rowell, Jasmine; Ross, Susan; Lau, Ching-In; Crompton, Tessa (Frontiers in Immunology, 2021)
Allergic asthma is a common inflammatory disease of the lungs and airways in which Th2 immune responses and inflammation are thought to be triggered by inhalation of environmental allergens. Many studies using mouse models, human tissues and genome wide association have indicated that Sonic Hedgehog (Shh) and the Hedgehog (Hh) signalling pathway are involved in allergic asthma and that Shh is upregulated in the lung on disease induction. We used a papain-induced mouse model of allergic airways inflammation to investigate the impact of systemic pharmacological inhibition of the Hh signal transduction molecule Smoothened on allergic airways disease induction and severity. Smoothened-inhibitor treatment reduced induction of Shh in the lung, and decreased serum IgE, and expression of Smo, Il4, Il13 and the Mucin gene Muc5ac in lung tissue. Smoothened inhibitor treatment reduced cellular infiltration of eosinophils, mast cells, basophils and CD4+ T-cells to the lung, and eosinophils and CD4+ T-cells in the bronchoalveolar lavage. In the mediastinal lymph nodes, Smoothened inhibitor treatment reduced the number of CD4+ T-cells, and their cell surface expression of Th2 markers ST2 and IL-4ra and expression of Th2 cytokines. Thus, overall pharmacological Smoothened inhibition attenuated T-cell infiltration to the lung and Th2 function, and reduced disease severity and inflammation in the airway.